Temporal force governs the microbial assembly associated with Ulva fasciata (Chlorophyta) from an integrated multi-trophic aquaculture system - Nguyen, Dzung; Ovadia, Ofer; Guttman, Lior (Frontiers in Microbiology, 2023)
Ulva spp., one of the most important providers of marine ecosystem services, has gained substantial attention lately in both ecological and applicational aspects. It is known that macroalgae and their associated microbial community form an inseparable unit whose intimate relationship can affect the wellbeing of both. Different cultivation systems, such as integrated multi-trophic aquaculture (IMTA), are assumed to impact Ulva bacterial community significantly in terms of compositional guilds. However, in such a highly dynamic environment, it is crucial to determine how the community dynamics change over time. In the current study, we characterized the microbiota associated with Ulva fasciata grown as a biofilter in an IMTA system in the Gulf of Aqaba (Eilat, Israel) over a developmental period of 5 weeks. The Ulva-associated microbial community was identified using the 16S rRNA gene amplicon sequencing technique, and ecological indices were further analyzed. The Ulva-associated microbiome revealed a swift change in composition along the temporal succession, with clusters of distinct communities for each timepoint. Proteobacteria, Bacteroidetes, Planctomycetes, and Deinococcus-Thermus, the most abundant phyla that accounted for up to 95% of all the amplicon sequence variants (ASVs) found, appeared in all weeks. Further analyses highlighted microbial biomarkers representing each timepoint and their characteristics. Finally, the presence of highly abundant species in Ulva microbiota yet underestimated in previous research (such as phyla Deinococcus-Thermus, families Saprospiraceae, Thiohalorhabdaceae, and Pirellulaceae) suggests that more attention should be paid to the temporal succession of the assembly of microbes inhabiting macroalgae in aquaculture, in general, and IMTA, in particular. Characterizing bacterial communities associated with Ulva fasciata from an IMTA system provided a better understanding of their associated microbial dynamics and revealed this macroalgae's adaptation to such a habitat.